2017
DOI: 10.4314/ejhs.v27i6.6
|View full text |Cite
|
Sign up to set email alerts
|

The use of first line Highly Active Anti-Retroviral Therapy (HAART) is not associated with QTC prolongation in HIV patients

Abstract: Background HAART has improved survival of HIV patients. Its contribution to the development of new cardiovascular abnormalities has generated much interest. This study aimed at determining the prevalence of QTc prolongation among HIV patients and determining the influence if any of the use of HAART on the QTc and on the risk of having QTc prolongation. Materials and Methods One hundred and fifty HIV positive subjects comprising 76 HIV positive subjects on HAART (Group A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…There is controversy about the impact of Efavirenz on QT length regardless of its subsequent clinical manifestations. 9,[16][17][18][19] Nevertheless, most studies such as the one by Charbit et al, found that prolonged QT is associated with conventional factors as well as chronicity of HIV infection rather than with ART drugs. 20 We found that Efavirenz regimen increased the length of corrected QT interval overall and in males while females were not affected.…”
Section: Discussionmentioning
confidence: 99%
“…There is controversy about the impact of Efavirenz on QT length regardless of its subsequent clinical manifestations. 9,[16][17][18][19] Nevertheless, most studies such as the one by Charbit et al, found that prolonged QT is associated with conventional factors as well as chronicity of HIV infection rather than with ART drugs. 20 We found that Efavirenz regimen increased the length of corrected QT interval overall and in males while females were not affected.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported an increased prevalence of QT prolongation among HIV‐infected individuals compared to uninfected controls possibly due to concurrent administration of QT‐prolonging medications as well as the effect of the virus itself on the QTc interval 9‐12 . Table 1 summarizes six studies which compared the prevalence of QTc prolongation between HIV‐infected individuals vs. an uninfected control group 9,10,13‐16 . QT prolongation is a precursor for life‐threatening arrhythmias including torsades de pointes.…”
Section: Qt Prolongation/risk Of Torsades De Pointesmentioning
confidence: 99%